The Using Communicative Language Teaching in the Online Class through Soundcloud, Zoom, and Google Classroom Applications - Faizal Amir; Astri Anggitasari (UM Purwokerto Press, 2022)
The schools have been implementing online learning during the pandemic. Teachers are required to be able to do online learning where these activities require the role of information and communication technology (ICT). Teachers cannot ensure that every student will understand the material taught during online learning. Therefore, the teacher must make several effective learning methods and approaches which can make students enthusiastic in learning and understanding the material presented. One approach that can be used by teachers is CLT (Communicative Language Teaching). Social interactions used in communicative language teaching can be done through dialogue, discussion, role-playing, etc. Nowadays, teachers implement many applications to support the online learning process, such as SoundCloud, Zoom, and Google Classroom. The use of those applications is to assist students in improving their skills. CLT can be used to teach many things such as vocabulary development, communication among instructors and learners, use of specialist language to a minimum, use of language (in the context of communication in general), use of Information Technology, information search skills, personal viewpoint argumentation abilities, nonverbal skills, and group networking skills.